2021
DOI: 10.1039/d1ra06151h
|View full text |Cite|
|
Sign up to set email alerts
|

X-ray absorption spectroscopy of exemplary platinum porphyrin and corrole derivatives: metal- versus ligand-centered oxidation

Abstract: Platinum L3-edge XAS and DFT calculations on three well-characterized Pt porphyrinoid complexes have provided detailed insights into metal- versus ligand-centered oxidation and ligand field effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Similar shifts based on ligand field strengths have also been noted at the L 2,3 -edges for third row metals; a recent example with platinum macrocyclic compounds showed that exchanging weaker field ligands (porphyrin, chloride) for stronger field ligands (corrole, pyridine, alkyl) in octahedral Pt(IV) compounds resulted in a 0.4 eV blue shift of the Pt L 3edge. 51 This shift was caused by the corresponding rise in the d-orbital manifold due to the strengthened ligand interactions. While the shift observed in this work between the iridium(III) species is larger (2 eV vs 0.4 eV), this can be attributed to the more dramatic ligand field strength difference of six chloride ligands versus three bidentate 2-phenylpyridine ligands.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar shifts based on ligand field strengths have also been noted at the L 2,3 -edges for third row metals; a recent example with platinum macrocyclic compounds showed that exchanging weaker field ligands (porphyrin, chloride) for stronger field ligands (corrole, pyridine, alkyl) in octahedral Pt(IV) compounds resulted in a 0.4 eV blue shift of the Pt L 3edge. 51 This shift was caused by the corresponding rise in the d-orbital manifold due to the strengthened ligand interactions. While the shift observed in this work between the iridium(III) species is larger (2 eV vs 0.4 eV), this can be attributed to the more dramatic ligand field strength difference of six chloride ligands versus three bidentate 2-phenylpyridine ligands.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Cl – is a weaker sigma donor compared to 2-phenylpyridine’s N py and C – ; the ppy ligand will result in higher energies for the empty e g d-orbitals compared to the chloride ligand and is consistent with the significant blue shift for both edges (Figure C). Similar shifts based on ligand field strengths have also been noted at the L 2,3 -edges for third row metals; a recent example with platinum macrocyclic compounds showed that exchanging weaker field ligands (porphyrin, chloride) for stronger field ligands (corrole, pyridine, alkyl) in octahedral Pt(IV) compounds resulted in a 0.4 eV blue shift of the Pt L 3 -edge . This shift was caused by the corresponding rise in the d-orbital manifold due to the strengthened ligand interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Similar shifts based on ligand field strengths have also been noted at the L 2,3 -edges for 3rd row metals; a recent example with platinum macrocyclic compounds showed that exchanging weaker field ligands (porphyrin, chloride) for stronger field ligands (corrole, pyridine, alkyl) in octahedral Pt(IV) compounds resulted in a 0.4 eV blue shift of the Pt L 3 -edge. 50 This shift was caused by the corresponding rise in the dorbital manifold due to the strengthened ligand interactions. While the shift observed in this work between the iridium(III) species is larger (2 eV vs 0.4 eV), this can be attributed to the more dramatic ligand field strength difference of six chloride ligands versus three bidentate 2phenylpyridine ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Similar shifts based on ligand field strengths have also been noted at the L 2,3 -edges for 3rd row metals; a recent example with platinum macrocyclic compounds showed that exchanging weaker field ligands (porphyrin, chloride) for stronger field ligands (corrole, pyridine, alkyl) in octahedral Pt(IV) compounds resulted in a 0.4 eV blue shift of the Pt L 3 -edge. 51 This shift was caused by the corresponding rise in the dorbital manifold due to the strengthened ligand interactions. While the shift observed in this work between the iridium(III) species is larger (2 eV vs 0.4 eV), this can be attributed to the more dramatic ligand field strength difference of six chloride ligands versus three bidentate 2phenylpyridine ligands.…”
Section: Resultsmentioning
confidence: 99%